Emerging materials for sample preparation. Issue 1 (13th November 2017) - Maya, Fernando; Palomino Cabello, Carlos; Ghani, Milad; Turnes Palomino, Gemma; Cerdà, Víctor
Abstract: This review provides an update on the implementation of emerging materials as sorbents for sample preparation in combination with chromatographic separation. We have focused on recent applications of metal–organic frameworks, layered double hydroxides, porous carbons obtained from polymers or biomass precursors, and silicates (clays and zeolites). The review is directed toward the strategies followed by the authors to engineer suitable supports enabling the application of materials with unconventional size and shape as high‐performance sorbents to explore new boundaries in sample pretreatment in manual or automated modes.